PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SIWA SMP PADA MATERI SPLDV - Wahyu Nurzaman; Nelly Fitriani; Gida Kadarisma; Wahyu Setiawan (IKIP Siliwangi, 2022)
This research is a classroom action research (CAR) which aims to examine the improvement of students’ mathematical understanding concept in the VIII grade SPLDV material at Junior High School 2 Saguling. This research was conducted on class VIII-A students in the 2020-2021 school years. The subjects of this study consisted of 17 students who belonge to group A in class VIII-A. the instruments used were test, interviews, and observation sheets given to teachers and students during classroom action research. The results showed that the aspect of students’ mathematical understanding abilities had increased because the actions given used a scientific approach and the questions on each test were in accordance with the indicators of the mathematical understanding ability. Based on the wprk indicators and processed resluts, it can be concluded that the mathematical understanding ability of grade VIII-A students of junior high school 2 Saguling can be through a scientific approach.